Perception of Digital Literacy of Arabic Language Education Students of Cipasung Islamic Institute (IAIC) - Susanti Wulandari (IAIN Ternate, 2021)
Digital literacy is an essential part of society in the 21st century era. The dynamics of the development of science and technology makes everyone have to adapt to digital technology, including students who will become the nation's next generation. This study aims to explore student perceptions of the importance of digital literacy for an educational institution. Descriptive research method is used to describe the results of student opinions which are explored through open questionnaires in the form of open-ended question. There are 85 students involved in this research. The findings show that students state the importance of digital literacy for an educational institution in terms of several aspects, namely the interests of the institution or the interests of the community as customers of an educational institution. This study presents several perceptions of digital literacy that can be used as a basis for an educator who will teach material about lectures in the field of education in the 21st century.Keywords: digital literacy, educational institution, perception, digital information system